P189 Development of Patient-Centred Outcomes for a Pleural Disease Service. (12th November 2015) - Smith, VM; Rowlandson, E; Early, F
Abstract : Introduction and aim: There are no standardised methods for developing patient-centred service outcomes. We recognised the need for locally derived outcomes for a new pleural disease service. Methods: A survey was administered to patients who had had a pleural or ascitic drain/aspiration. The survey combined open and closed questions e.g What is important to you? We carried out emotional mapping in half of the subjects with the aim of gaining more in depth information on patient experience (see NHS institute website). We held a structured discussion with one patient's relative to explore the themes more broadly. Patients were identified from three acute areas, over a six week period. They were typical of patients from the medical take and respiratory ward. The survey and emotional mapping were carried out with patients face-to-face by the project lead. Themes from the survey and emotional mapping were identified. The most common themes from the data were discussed in the structured discussion. Results: 18 patients were surveyed (4 after ascitic procedures), 9 had emotional mapping. The mean overall service rating was 4/5. The graph above represents both responses to the question 'What is important to you?' and themes that emerged from emotional mapping. More detailed insight was gained from the discussion with one patient's relative, this was triangulated with the other data to give a clearer picture of what was most important to patients. Similar themes were combined to form 5 final patient-centred outcomes that were important to patients (see Figure 1 attached). E.g. 'Be treated as an INDIVIDUAL' encompassed good interpersonal relationships and personal choice, and 'Receive the RIGHT INFORMATION' for consent, medical care and managing waiting. Discussion: These five outcomes were developed for a specific service. The data has come from a relatively small number of patients from a specific cohort, but they seem credible, and may be more widely applicable. The next step is to measure the service against these outcomes before and after the. A new patient survey has been designed to measure these outcomes. It will be administered before and after the start of the new service.